Implementasi Program Desa Perempuan Indonesia Maju Mandiri (Prima) Dalam Upaya Pemberdayaan Perempuan Di Kalurahan Piyaman, Wonosari, Gunungkidul - Nursanti, Vivi; Karna Djaja, Djuniawan; Apriyani, Tanti (LPPM STIA Lancang Kuning Dumai, 2025)
This research aims to analyze the implementation of the Desa PRIMA program in efforts to empower women in Kalurahan Piyaman. Additionally, it seeks to identify the supporting and inhibiting factors in the programs implementation. The study employs a qualitative descriptive research method. The research location is Kalurahan Piyaman, and data is collected through interviews, observations, and documentation. Informants were selected using purposive sampling. The data sources consist of primary and secondary data, and data validity was tested using source, technique, and time triangulation. Data analysis followed the three stages proposed by Miles and Huberman data reduction, data display, and conclusion drawing. The research results show that the implementation of the Desa PRIMA program has not been carried out optimally, which has also impacted women's empowerment efforts, making them less effective. The supporting factors include the availability of facilities and savings and loan services. In contrast, the inhibiting factors consist of low member motivation, the inability to conduct online marketing and budget limitations.